Metode dan Media Penyuluhan Budidaya Ikan Hias di Kecamatan Beringin Kabupaten Deli Serdang Provinsi Sumatera Utara - Agung Yunanto; Budhi H. Iskandar; Rinda Noviyanti (EduInovasi: Journal of Basic Educational Studies, 2024)
isheries extension is one of the efforts to increase productivity, business efficiency, income, and welfare for fish farmers. The learning process is carried out so that the main actors and fisheries business actors are willing and able to help and organize themselves in accessing market information, technology, capital, and other resources. Extension methods and media are two factors that influence the success of ornamental fish cultivation extension. The types of counseling methods that are usually carried out by fisheries extension agents in Beringin District, Deli Serdang Regency are individual counseling, group counseling, and interviews. While the counseling media that are usually delivered such as broadcast, printed, and audible, This study aims to analyse the counselling methods and media used in ornamental fish cultivation counselling in Beringin District, Deli Serdang Regency. Using path analysis with 90 respondents from ornamental fish cultivators in Beringin District, Deli Serdang Regency. The results showed that the extension method has an influence of 33,5% on the success of ornamental fish farming, whereas group meetings are the type of extension method that has the highest correlation of 0,467 on the success of ornamental fish farming. While extension media has a 22,4% influence on the success of ornamental fish cultivation extension, broadcast media has a correlation of 0,428.